Partnered Women's labour supply and child care costs in Australia: Measurement error and the child care price - Ling, Anthony; Breunig, Robert; Gong, Xiaodong (My University, 2012)
We show that measurement error in the constructed price of child-care can explain why previous Australian studies have found partnered women's labour supply to be unresponsive to child-care prices. Through improved data and improved construction of the child-care price variable, we find child-care price elasticities that are statistically significant, negative and in line with elasticities found in other developed countries.
Economic Record
Keywords: Gender -- Female; Child Care; Employment -- Labour force supply; Families -- Partners; Families and relationships; Gender; Labour market; Families; Child Care; Gender; Employment; Partners; Female; Labour force supply; Families and relationships; Gender; Employment and unemployment